Factors influencing tax compliance from the perspective of young workers: evidence from Malaysia / Siti Nurhazwani Kamarudin ... [et al.] - Kamarudin, Siti Nurhazwani; Azman, Aiman Faiz; Abdul Rasit, Zarinah; Mohd Nasir, Noor Emilina (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
As young workers represent 63.75% of the total labour workforce, ensuring tax compliance among this demographic is imperative to mitigate revenue leakage. This study aimed to ascertain the factors that influenced tax compliance among young workers, focusing on tax knowledge, tax morale, tax penalties, and tax complexity within the framework of the theory of planned behaviour. The data was gathered through online survey questionnaires disseminated via WhatsApp, email, and social media to young taxpayers in Malaysia. Analysis of 384 samples utilising multiple regression analysis revealed that tax penalties and tax complexity exert significant influence on tax compliance, whereas tax knowledge and tax morale were vice versa. The evidence implied that there is better compliance with the tax laws by young workers to avoid punishments with less complexity of the tax system. The research provides empirical evidence that underscores the importance of stringent enforcement of penalties and simplification of the tax system to foster greater compliance among young workers, thereby bolstering tax revenues for the government.